Tubulin polymerization disrupts cardiac β-adrenergic regulation of late INa - Dybkova, Nataliya; Backs, Johannes (Cardiovascular research, 2014)
Aims: The anticancer drug paclitaxel (TXL) that polymerizes microtubules is associated with arrhythmias and sinus node dysfunction. TXL can alter membrane expression of Na channels (NaV1.5) and Na current (INa), but the mechanisms are unknown. Calcium/calmodulin-dependent protein kinase II (CaMKII) can be activated by β-adrenergic stimulation and regulates INa gating. We tested whether TXL interferes with isoproterenol (ISO)-induced activation of CaMKII and consequent INa regulation. Methods and results: In wild-type mouse myocytes, the addition of ISO (1 µmol/L) resulted in increased CaMKII auto-phosphorylation (western blotting). This increase was completely abolished after pre-treatment with TXL (100 µmol/L, 1.5 h). The mechanism was further investigated in human embryonic kidney cells. TXL inhibited the ISO-induced β-arrestin translocation. Interestingly, both knockdown of β-arrestin2 expression using small interfering RNA and inhibition of exchange protein directly activated by cAMP (Epac) blocked the ISO-induced CaMKII auto-phosphorylation similar to TXL. The generation of cAMP, however, was unaltered (Epac1-camps). CaMKII-dependent Na channel function was measured using patch-clamp technique in isolated cardiomyoctes. ISO stimulation failed to induce CaMKII-dependent enhancement of late INa and Na channel inactivation (negative voltage shift in steady-state activation and enhanced intermediate inactivation) after pre-incubation with TXL. Consistent with this, TXL also inhibited ISO-induced CaMKII-specific Na channel phosphorylation (at serine 571 of NaV1.5). Conclusion: Pre-incubation with TXL disrupts the ISO-dependent CaMKII activation and consequent Na channel regulation. This may be important for patients receiving TXL treatments, but also relevant for conditions of increased CaMKII expression and enhanced β-adrenergic stimulation like in heart failure.